Growth and yield potential of sludge-based organic fertilizers on bell pepper Capsicum annum (Asian Journal of Agriculture, 2024)
Abstract. Balkrishna A, Gautam AK, Sharma N, Arya V, Khelwade V. 2024. Growth and yield potential of sludge-based organic fertilizers on bell pepper  Capsicum annum. Asian J Agric 8: 18-24. This study investigated the effects of different organic fertilizers on bell pepper’s growth and yield potential (Capsicum annum L.). A total of six fertilizer treatments and one control in three replications were analyzed using a Randomized Complete Block Design (RCBD). The effects of fertilizer application on plant parameters were evaluated on plant height, total number of leaves, leaf area, total number of branches, number of flowers, number of fruits, average fruit weight, average fruit diameter, total yield per plot, and total yield at every 30 days after sowing. All organic fertilizers positively impacted the growth and yield of the Capsicum crop. The experimental results revealed that treatment T1 (Jaivik Prom), T4 (Jaivik Poshak), and T6 (Jaivik Prom+ Jaivik Khad) displayed significant performance in all parameters, where T5 (Jaivik Khad) performed well in improving leaf area, fruit weight and total yield per plot. In addition, other treatments also exhibited a notable effect on different plant parameters. Based on these results, it was found that all organic fertilizers can potentially improve the growth and yield of Capsicum. From this, it was concluded that the sewage sludge processing into organic fertilizers highlighted the safer and environmentally friendly way of managing Ganga sludge. Further research should be conducted on different aspects of sludge-based organic fertilizers like processing, production and field application on more field crops.
Keywords: Agriculture, Capsicum, growth parameters, organic fertilizers, sludge management, yield